Numerical study on the thermal performance of phase change materials wall by radiative cooling. (October 2022) - Yu, Cairui; Shen, Dongmei; Wang, Wanfen; Song, Xinwei; Xin, Jin; Cai, Luxiu; Tu, Jinsong
Highlights: A wall incorporating phase change materials (PCM) and radiation cooling was proposed. The thermal performance of the wall was investigated all the day. The energy saving of the wall with different PCM positions were compared. Abstract: The present study built a type of wall composed of phase change materials (PCMs), micro-channel heat pipe, and a radiative plate, the combination of which makes use of the radiative cooling (RC) technology of the radiative plate that ultimately releases the heat of PCMs at night. First, the new wall (RC-PCM) testing rig was built and tested, after which the experimental and numerical results were compared. Furthermore, to compare to the thermal performance of the RC-PCM wall, Brick and PCM walls of the same size as the RC-PCM wall were established as reference walls. Second, the thermal evaluation of RC-PCM wall was investigated using a numerical method. Finally, the RC-PCM wall thermal performance was investigated by varying the PCM position of the load-bearing wall, from which the numerical results of the two were compared. The research results indicated that: (1) the interior surface temperature of the RC-PCM wall was lower than that of the Brick and PCM walls, where PCM availability was 7% higher than that of the PCM wall. (2) The indoor thermal comfort of PCM on the indoor side is higher than that of PCM on the outdoor side. (3) The RC-PCM-in (PCM layer is located inside load-bearing wall) showed certain advantages in the interior surface temperature and PCM availability as compared to the RC-PCM wall. In conclusion, RC-PCM wall exhibited good potential in engineering applications.